The gull next door : a portrait of a misunderstood bird - Taylor, Marianne (Oxfordshire Princeton University Press, 2020)
A uniquely personal meditation on Britain's gulls by one of today's leading wildlife writers from a distance, gulls are beautiful symbols of freedom over the oceanic wilderness. Up close, however, they can be loud, aggressive and even violent. Yet gulls fascinate birdwatchers, and seafarers regard them with respect and affection. The Gull Next Door explores the natural history of gulls and their complicated relationship with humans.Marianne Taylor grew up in an English seaside town where gulls are ever present. Today, she is a passionate advocate for these underappreciated birds. In this book, Taylor looks at the different gull species and sheds light on all aspects of the lives of gulls--how they find food, raise families, socialize and migrate across sea, coastland and countryside. She discusses the herring gull, Britain's best-known and most persecuted gull species, whose numbers are declining at an alarming rate. She looks at gulls in legend, fiction and popular culture, and explains what we can do to protect gull populations around the world.The Gull Next Door reveals deeper truths about these remarkable birds. They are thinkers and innovators, devoted partners and parents. They lead long lives and often indulge their powerful drive to explore and travel. But for all these natural gifts, many gull species are struggling to survive in the wild places they naturally inhabit, which is why they are now exploiting the opportunities of human habitats. This book shows how we might live more harmoniously with these majestic yet misunderstood birds.--
Includes index.
Keywords: Gulls; Gulls; Gulls